2015
DOI: 10.1161/circresaha.116.302953
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Controls of Arterial Morphogenesis

Abstract: Formation of arterial vasculature, here termed arteriogenesis, is a central process in embryonic vascular development as well as in adult tissues. While the process of capillary formation, angiogenesis, is relatively well understood, much remains to be learned about arteriogenesis. Recent discoveries point to the key role played by vascular endothelial growth factor receptor 2 (VEGFR2) in control of this process and to newly identified control circuits that dramatically influence its activity. The latter can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 150 publications
2
123
0
Order By: Relevance
“…30,31 Pericytes and smooth muscle cells play important roles in regulating angiogenesis and BBB leakage. 34,[51][52][53] We found that ADAMTS13 deficiency in mice increased the ischemic damage to smooth muscle cells and pericytes, resulting in reduced pericyte and smooth muscle cell coverage on microvessels during the later phase of stroke. These effects were accompanied by reduced expression of the BBB tight junction and basement membrane proteins.…”
Section: Discussionmentioning
confidence: 79%
“…30,31 Pericytes and smooth muscle cells play important roles in regulating angiogenesis and BBB leakage. 34,[51][52][53] We found that ADAMTS13 deficiency in mice increased the ischemic damage to smooth muscle cells and pericytes, resulting in reduced pericyte and smooth muscle cell coverage on microvessels during the later phase of stroke. These effects were accompanied by reduced expression of the BBB tight junction and basement membrane proteins.…”
Section: Discussionmentioning
confidence: 79%
“…ERK signaling is an important mediator of angiogenesis and arteriogenesis downstream of VEGFR2 activation, and VEGF-B increases ERK1/2 phosphorylation in the heart (10,18). Here were found that DOX treatment significantly reduced ERK1/2 phosphorylation, which was reversed by VEGF-B (Fig.…”
Section: Dox-induced Cardiac Atrophy Is Inhibited By Vegf-bmentioning
confidence: 62%
“…These findings raise the interesting possibility that the reactivation of developmental processes controlling bone angiogenesis could be utilized to prevent agerelated or disease-induced bone loss. Likewise, the reactivation of pathways promoting artery formation during development (Herbert and Stainier, 2011;Simons and Eichmann, 2015) might potentially prove useful for the treatment of avascular necrosis, which involves the death of bone tissue due to a lack of local blood supply (Eltzschig and Eckle, 2011;Silvestre et al, 2013), although whether findings in the skeletal system of mice are applicable to humans needs to be investigated. Despite many open questions and caveats, we are presented with the exciting opportunity to investigate the precise role of bone blood vessels and EC subpopulations in a variety of physiological and pathobiological settings, which will undoubtedly enhance our mechanistic understanding of the cellular and molecular processes in the developing, adult, ageing and diseased skeletal system.…”
Section: Future Perspectivesmentioning
confidence: 99%